An evaluation of the impact of the Social Mobility Foundation Programmes on Education Outcomes - Claire Crawford; Ellen Greaves; Wenchao Jin (Institute for Fiscal Studies (IFS), 2015)
The Social Mobility Foundation (SMF) is a charity that aims to make apractical improvement to social mobility in the UK by encouraging and supporting access to "high-status" universities and professional occupations for high attaining pupils from disadvantaged backgrounds. The SMF's programmes are targeted to those who are eligible for free school meals (or, in earlier cohorts, the educational maintenance allowance) and, amongst the latest cohorts, to those who are in the first generation of their family to attend higher education and who attend a relatively disadvantaged school. The SMF's current programmes feature four key elements of mentoring, internships, university application support (including trips to universities and assistance with writing their personal statement, tests and interviews) and skills development workshops. Their main programme is known as the Aspiring Professionals Programme (APP). In recent years, they have also added more specialist programmes run in partnership with other organisations. For example, they run the J.P. Morgan Residential Programme targeted to those living outside London who are interested in a career in banking and finance. University participation, and especially participation at a high-statusinstitution in a relevant subject, is a potentially important intermediate step towards accessing the type of professional occupations the SMF targets. This report therefore evaluates the impact of the SMF's programmes on university participation overall and at high-status institutions. It also assesses its effecton subject choice (although this is not explicitly targeted by the SMF's programmes). The impact of the SMF's work on post-graduation education and employment choices, and in particular occupation outcomes, will be evaluated in future by the Institute for Fiscal Studies (IFS) as the required data become available. This evaluation compares the education outcomes of SMF participants (collected by SMF via participant questionnaires) with outcomes for a group of pupils with similar observable characteristics (such as performance at secondary school and neighbourhood context), observed in administrative data. This report focuses on the education outcomes for four cohorts of participants with the SMF: the first cohort we look at entered the programme in 2009 (referred to as the 2009 cohort), the second in 2010, the third in 2011 and the fourth in 2012. [...]
Keywords: 330